The Meaning of Caregiving in Korean Television Dramas with Protagonists with Mental or Developmental Disorders - Min Joo Lee (Series. International journal of tv serial narratives, 2025)
This article examines underlying themes in popular Korean television dramas’ depictions of mental and developmental disorders. I specifically focus on three television dramas whose plots center around various mental and developmental disorders: It’s Okay, That’s Love (2014), It's Okay Not to Be Okay (2020), and Extraordinary Attorney Woo (2022). I utilize Korean scholar Eunjung Kim’s theoretical framework of “curative violence” to examine how these dramas concurrently move beyond and perpetuate the “curative violence” practiced in Korea throughout its modern history against disabled and disordered subjects. I argue that the above three dramas diverge from the trend of problematic depictions of disorders in Korean documentaries, films, and novels that other disability scholars and activists have analyzed and critiqued in depth. The three dramas successfully contest the false and homogenizing equivalence between caregivers always being the non-disordered and the cared always being the disordered, which perpetuates social discrimination and stigma against people with mental and developmental disorders. Instead, the dramas complicate the binary of the caregiver versus the cared and that between the disordered and the non-disordered through camera techniques and plot devices and thereby effectively contests some of the premises for Korean societal prejudice against those with mental or developmental disorders.